2009
DOI: 10.1021/jp903208k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Ethylene Glycol Dimethacrylate Glass Former: Influence of Different Crystallization Pathways

Abstract: The crystallization induced by different thermal treatments of a low molecular weight glass former, ethylene glycol dimethacrylate (EGDMA), was investigated by dielectric relaxation spectroscopy (DRS) and differential scanning calorimetry (DSC). The fully amorphous material, dielectrically characterized for the first time, exhibits three relaxation processes: the alpha-relaxation related to dynamic glass transition whose relaxation rate obeys a Vogel-Fulcher-Tamman-Hesse (VFTH) law and two secondary processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 62 publications
6
21
0
Order By: Relevance
“…Equation 6 explains the linear dependence of ∆h cr with temperature and allows determining ∆c p ) c pl -c ps from the experimental results, obtaining a value of ∆c p ) c pl -c ps ) 138.6 J · (K · mol) -1 , slightly higher than the heat capacity difference between the liquid and the glass (∆c p (T g ) ) 114.9 J · (K · mol) -1 determined in heating scans). 1 The fit of eq 6 to the experimental values yields h l (T m ) -h s (T m ) ) 21.4 kJ · mol -1 , close to the values determined by integration of the melting endotherms detected during the heating scans; however, it can not be unambiguously concluded that complete crystallization from the melt was attained as probed by DSC.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Equation 6 explains the linear dependence of ∆h cr with temperature and allows determining ∆c p ) c pl -c ps from the experimental results, obtaining a value of ∆c p ) c pl -c ps ) 138.6 J · (K · mol) -1 , slightly higher than the heat capacity difference between the liquid and the glass (∆c p (T g ) ) 114.9 J · (K · mol) -1 determined in heating scans). 1 The fit of eq 6 to the experimental values yields h l (T m ) -h s (T m ) ) 21.4 kJ · mol -1 , close to the values determined by integration of the melting endotherms detected during the heating scans; however, it can not be unambiguously concluded that complete crystallization from the melt was attained as probed by DSC.…”
Section: Discussionsupporting
confidence: 70%
“…The difference in the crystallization behavior of EGDMA between the two techniques was also found in a previous work under the same temperature protocols. 1 While the estimated induction time for cold-crystallization, in the studied temperature interval, increases with a decrease in temperature, for melt-crystallization that covers a more extended temperature range, and t 0 generally follows the temperature dependence observed for the experimental time of onset for crystallization shown earlier in the inset of Figure 6b.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations